2015
DOI: 10.1039/c5tc02399h
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic properties and magnetoelectric coupling in Fe/Co co-doped Bi3.25La0.75Ti3O12 ceramics

Abstract: Good ferroelectricity, weak ferromagnetism and the sign of magnetoelectric coupling are obtained simultaneously in Bi3.25La0.75(Ti2.75Fe0.125Co0.125)O12 ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 52 publications
6
11
0
Order By: Relevance
“…Similar results have been observed in X-ray diffraction studies by Ruixia Ti et al [46], where the authors observed the impurity peaks in Fe/Co co-doped B3.25La0.75Ti3O12 ceramic system. They have observed weak impurity peaks related to Bi2Ti2O7 (for x=0.01) and Bi2O3 (for x=0.05).…”
Section: Structural Studies Of Bi4ti3o12supporting
confidence: 89%
See 2 more Smart Citations
“…Similar results have been observed in X-ray diffraction studies by Ruixia Ti et al [46], where the authors observed the impurity peaks in Fe/Co co-doped B3.25La0.75Ti3O12 ceramic system. They have observed weak impurity peaks related to Bi2Ti2O7 (for x=0.01) and Bi2O3 (for x=0.05).…”
Section: Structural Studies Of Bi4ti3o12supporting
confidence: 89%
“…Similar results of Raman spectroscopy have been observed for Fe/Co co-doped B3.25La0.75Ti3O12 ceramics by Ruixia Ti et al [46].…”
Section: Structural Studies Of Bi4ti3o12supporting
confidence: 88%
See 1 more Smart Citation
“…The O c peak is usually attributed to chemisorbed oxygen on the surface of the nanostructures, such as adsorbed −CO 3 , H 2 O, or O 2 . Ti et al . suggested the possible ME coupling mechanism that associated with binding effect of magnetic interaction on the migration of charged defects, especially oxygen vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a 2P r~1 0.6 µC/cm 2 was observed in Bi 4.25 Gd 0.75 Fe 0.5 Co 0.5 Ti 3 O 15 , at 180 kV/cm [136]. Owing to decreasing leakage current (La /Sr-doping) and improving magnetic properties (Co-doping), La /Sr and Co co-doped BFTO-n ceramics or films have recently become a focus of attention [139][140][141][142][143], and can show saturated FE hysteresis loops with 2P r~2 0-50 µC/cm 2 and large saturation magnetization with~10 emu/cm 3 for film and~1 emu/g for ceramic.…”
Section: Chemical Modificationmentioning
confidence: 99%